Gold nanospheres and gold nanostars immobilized onto thiolated eggshell membranes as highly robust and recyclable catalysts. (4th August 2017) - Li, Yunhua; Geng, Xi; Leng, Weinan; Vikesland, Peter J.; Grove, Tijana Z.
Abstract : This study describes a facile method for immobilizing nanoparticles with different morphologies onto a biopolymeric fibrous network – eggshell membranes (ESM). Abstract : This study describes a facile method for immobilizing nanoparticles with different morphologies onto a biopolymeric fibrous network – eggshell membranes (ESM). Solution processing of the ESM to liberate inherent thiols enabled efficient immobilization of gold nanoparticles without the use of additional, external crosslinkers. The catalytic activity of such prepared membranes was evaluated through the reduction of p -nitrophenol (PNP) to p -aminophenol (PAP). The resulting biohybrid materials exhibited enhanced stability and reusability over colloidal nanoparticle suspensions and retained their desirable catalytic activity even after ten reaction cycles and a period of one hundred days.